Assessing habitat suitability for wintering geese by using Normalized Difference Water Index (NDWI) in a large floodplain wetland, China. (March 2021) - Teng, Jiakun; Xia, Shaoxia; Liu, Yu; Yu, Xiubo; Duan, Houlang; Xiao, Han; Zhao, Chuanpeng
Highlights: NDWI can reflect the spatio-temporal hydrological dynamics in the large floodplain. Significant correlations exist among NDWI, water level and goose occurrence. The suitable habitats for geese can be extracted quickly by using NDWI range. Abstract: Hydrological condition is one of the most important factors affecting the abundance and distribution of waterbirds in large freshwater floodplains, as it influences their habitat and food availability. The hydrological condition is commonly indicated with site-based hydrological data such as water level. Site-based data have high temporal resolution but are less effective to represent the spatial characteristics, a requirement for ecological/habitat models. In this study, we propose a method to identify suitable habitats for wintering geese based on the Normalized Difference Water Index (NDWI) derived from Sentinel-2 satellite images. The relationships between NDWI, water level and geese occurrence were analyzed. The results showed that the NDWI of Poyang Lake can explain 75% of the changes in water level and at least 42% of the geese occurrence during wintering periods (with the exception of February 2019). The monthly NDWI optimal ranges suitable for wintering geese were identified to be from −0.12 to 0 and suitable NDWI threshold range is from −0.27 to 0.14. Based on this threshold range, we identified the suitable habitat for geese and found that the suitable habitat area first increased and later decreased during the whole wintering periods, following an inverted U-shaped dynamic. We concluded that NDWI can be used to improve distribution models of waterbird species to support their protection and wetland management.